Morphological characterization of point patterns - Mecke, Klaus; et al. (Biometrical Journal, 2005)
The paper describes the statistical estimation of the new characteristics. Some examples illustrate their application in the exploratory analysis of point patterns of tree positions in forests, in comparison to results obtained by means of second-order and distance characteristics.
Keywords: distance characteristic; Euler characteristic; forest; integral geometry; point process; second-order characteristic; statistical estimation